Factors Affecting Vagus Nerve Stimulation Outcomes in Epilepsy - Mehdi Abbasi; Atie Moghtadaie; Seyed Amir Miratashi Yazdi (Neurology Research International)
Epilepsy as a common neurological disease is mostly managed effectively with antiepileptic medications. One-third of patients do not respond to medical treatments requiring alternative therapies. Vagus nerve stimulation (VNS) has been used in the last decades for the treatment of medically resistant epilepsy. Despite the extensive use of VNS in these patients, factors associated with clinical outcomes of VNS remain to be elucidated. In this study, we evaluated factors affecting VNS outcomes in epileptic patients to have a better understanding of patients who are better candidates for VNS therapy. Several databases including PubMed, Scopus, and Google Scholar were searched through June 2020 for relevant articles. The following factors were assessed in this review: previous surgical history, age at implantation and gender, types of epilepsy, duration of epilepsy, age at epilepsy onset, frequency of attacks, antiepileptic drugs, VNS parameters, EEG findings, MRI findings, and biomarkers. Literature data show that nonresponder rates range between 25% and 65%. Given the complexity and diversity of factors associated with response to VNS, more clinical studies are needed to establish better paradigm for selection of patients for VNS therapy.